PERAN WANITA KARIER DALAM MENANAMKAN PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI INSTITUT AGAMA ISLAM NEGERI (IAIN) BONE - M, Rahmawati; Samsinar, Samsinar (JURNAL AL-QAYYIMAH, 2021)
AbstrakThis article discusses the role of career women in planting character education in early childhood at Islamic State Institute of Bone (IAIN Bone) and their obstacles. The type of this research is a qualitative research and the authors use field research methods using psychological and sociological approaches. Data was collected by using interviews, documentation, observation. The data obtained, processed using the method of reduction, presenting data, and verifying data, then analyzed using qualitative analysis techniques inductively and deductively.The results showed that the efforts of career women at IAIN Bone in planting character education in early childhood was promised. By using methods of habituation, exemplary, discipline and accompanied by approaches so that interactions between children and parents were easier to give love, foster morals and build good communication.